Unveiling the Impact of 0–20 Gpa Hydrostatic Pressure on the Physical Properties of (Cs2HfCl6) Double Perovskite - Umar Farooq; Nabeel Israr; Belqees Hassan; Ali Alnakhlani; Mohamed Kallel; Wasif ur Rehman; Yong-Long Wang (Crystals)
The current work determines the physical properties of Cs2HfCl6 photovoltaic compounds including their structural, electronic, and optical behavior, utilizing the DFT approach. The simulated Cs2HfCl6 lattice constants, cell volumes, and bond lengths decrease as the pressure increases from 0 to 20 GPa. The band structure analysis reveals that the calculated under-pressure (0–20 GPa) of Cs2HfCl6 is semiconducting with a flexible indirect bandgap (5.44, 2.76, 2.02, 1.45, and 0.99) eV. The electronic bandgap diminishes (0–20 GPa), transitioning the compound from the UV to the visible spectra. This alteration improves the transition from the VBM to the CBM, hence augmenting the optical effectiveness. Concurrently, the dielectric function escalates, enhancing the absorption and conductivity, and causing a red shift in the optical spectra, while diminishing the reflection in the visible spectra. Our findings on the hydraulic pressure (0–20 GPa) and the electrical and optical properties indicate that Cs2HfCl6 may be utilized in the development of next-generation solar cells, LEDs, UV sensors, and high-pressure optical instruments.